Bacteriophage gene products as potential antimicrobials against tuberculosis. (13th May 2019) - Puiu, Maria; Julius, Christina
Abstract : Tuberculosis (TB) is recognised as one of the most pressing global health threats among infectious diseases. Bacteriophages are adapted for killing of their host, and they were exploited in antibacterial therapy already before the discovery of antibiotics. Antibiotics as broadly active drugs overshadowed phage therapy for a long time. However, owing to the rapid spread of antibiotic resistance and the increasing complexity of treatment of drug-resistant TB, mycobacteriophages are being studied for their antimicrobial potential. Besides phage therapy, which is the administration of live phages to infected patients, the development of drugs of phage origin is gaining interest. This path of medical research might provide us with a new pool of previously undiscovered inhibition mechanisms and molecular interactions which are also of interest in basic research of cellular processes, such as transcription. The current state of research on mycobacteriophage-derived anti-TB treatment is reviewed in comparison with inhibitors from other phages, and with focus on transcription as the host target process.